Induksi PLB Anggrek Vanda sumatrana Schltr. Liar Pada Media MS dengan Penambahan BAP dan NAA serta Ploidisasi dengan Kolkisin - Hanifah - Aini; Mansyurdin - Mansyurdin; Suwirmen - Suwirmen (Jurnal Biologi Universitas Andalas, 2015)
The study about PLB induction of wild Vanda sumatrana Schltr. on MS media suplement with BAP and NAA and ploidisation by colchicine treatment was conducted from December 2014 until November 2015 at the Laboratory of Genetics and Cell Biology and Laboratory of Plant Physiology and Tissue Culture, Biology department, Faculty of Mathematic and Natural Science, Andalas University, Padang. The study aimed to 1) knowing the best concentration of 6-Benzyl amino purin (BAP) and α-Naphtalene acetic acid (NAA) for Protocorm Like Bodies (PLB)  induction from shoot tip of V. sumatrana, 2) knowing the PLB response of V. sumatrana to concentrations and soak period of colchicine and 3) find the effective concentrations and soak period of colchicine to induce tetraploid on PLB of V. sumatrana. Shoot tips from in-vitro cultured of V. sumatrana  were subcultured on Murashinge and Skoog (MS) medium supplement with 3 mg/l BAP + 0,5 mg/l NAA, 3 mg/l BAP and 1,5 mg/l BAP. PLB of diploid V. sumatrana from the best treatment were soaked in 0.05% and 0.1% colchicine for 24 and 48 hours respectively in MS liquid medium, as control were set PLB without colchicine treatment. The results showed that MS medium supplemented with 1.5 mg/l BAP was the best formula to induce PLB. The highest percentage of survival rate of PLB and percentage of survived PLB regenerated shoot was obtained from 0.05% colchicine with 24 hours soak period treatment. The effective treatment to induce tetraploid on PLB of V. sumatrana Schltr. was obtained from 0.05% colchicine solution for 24 hours soak period.